Numerical and Experimental Investigation of Aerodynamic Characteristics of Morphing Trailing Edge Wings in The Application of MAV - Kumar, S Kishore; Pendyala, Srinivas (International Journal of Integrated Engineering, 2023)
The primary focus of this study is on the aerodynamic performance of a NACA 23012 airfoil coupled with various surfaces in numerical and experimental studies of morphing wings motivated by biomimicry. The evaluation of airfoils with various trailing edge morphologies in pressure distribution, lift and drag forces. The experimental work was conducted in a low-speed wind tunnel at different angles of attack ranging from 00 to 160 at low Reynolds number (Re)=34000, 68000 and 98600 respectively. Additionally, the MTE position was tested at 25% chord length from the trailing edge with varying MTE deflection ranging from 50, 70, and 100. Measures of aerodynamics that have been thoroughly researched, such as pressure distribution, velocity profiles, and lift and drag forces. The findings demonstrate how strongly the morphing trailing edge profiles influence the aerodynamic forces. It was found that as MTE deflection increases, high lift coefficient values are produced compared to conventional airfoils, boosting the aerodynamic efficiency of the micro aerial vehicle. And this study suggests that it is necessary to postpone the flow separation to attain the best aerodynamic performance, but micro aerial vehicles can only consider small deflections when flying.